Tuberculosis Transmission in a Primary School and a Private Language School. An Estimation of Infectivity - Debulpaep, Sara; Dreesman, Alexandra; Dirix, Violette; Toppet, Veronique; Wanlin, Maryse; Geysens, Lies; Arrazola de Oñate, Wouter; Fauville, Maryse; Mascart, Françoise; Levy, Jack; Mouchet, Françoise (Frontiers in Pediatrics, 2020)
Introduction Belgium is a country with low incidence of tuberculosis (TB) and a very low number of TB cases in children. Children in contact with an adult smear-positive TB case are at high risk of transmission. Early diagnosis is important as young children have a significant predisposition of developing TB disease. We describe two outbreaks after exposure to respectively two teachers with smear-positive pulmonary TB: one in a primary school, a nursery teacher, and another in a private language school. Methods An exposure investigation was carried out in both index cases household and school, according to the stone-in-the-pond principle. The tuberculin skin test was used as a screening tool. The time elapsed between TB diagnosis in the index case and contact investigation was respectively one week and three weeks. Results Index cases showed a transmission rate of respectively 13% and 40% in their classes at school, defined as casual contacts. The proximity of contact increased the risk of infection. TB disease was observed in respectively 4% and 11% of all the casual contacts; all of them were children younger than five years old. TB-infected and children with active TB disease had good compliance with recommended treatment. Uptake of chemoprophylaxis during the “window period” was poor, respectively only 32% to 42%. Discussion The World Health Organization recommends to screen all young children who have close contact with a person affected by pulmonary TB and to initiate LTBI treatment even before infection can be demonstrated, after ruling out active TB disease. Despite this knowledge, a small percentage of the children younger than five years with no proof of infection was treated with the proposed chemoprophylactic treatment, in both cases. Conclusion This exposure investigation of two teachers detects high transmission among family contacts and school casual contacts. Recommendations for chemoprophylactic treatment in children less than five years showed low compliance, reflecting the difficulty of communication in a school outbreak. This approach could be improved and evaluated by National TB Control Programs, involving public health services. Authorities play a role in raising public awareness about the risks of TB for young children.